Meigs’ syndrome with elevated CA-125 and HE-4: a case of luteinized fibrothecoma - Danilos, Jaroslaw (Prz Menopauzalny, 2015)
Presence of fibrothecoma is not usually accompanied by elevated levels of tumor markers. In recent years, however, there have been isolated reports of fibrothecoma and Meigs’ syndrome, accompanied by an increase in tumor markers. We present a case of fibrothecoma with Meigs’ syndrome and elevated levels of both CA-125 (cancer antigen 125) and HE-4 (human epididymis protein 4). In this paper, we present a case of Meigs’ syndrome associated with an increased CA-125 and HE-4 level due to ovarian fibrothecoma.